2022
DOI: 10.3389/fimmu.2022.867693
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peripheral Immune Cell Counts on the Risk of Multiple Sclerosis: A Mendelian Randomization Study

Abstract: ObjectivesMultiple sclerosis (MS) is a complex central nervous system (CNS) demyelinating disease, the etiology of which involves the interplay between genetic and environmental factors. We aimed to determine whether genetically predicted peripheral immune cell counts may have a causal effect on MS.MethodsWe used genetic variants strongly associated with cell counts of circulating leukocyte, lymphocyte, monocyte, neutrophil, eosinophil, and basophil, in addition to some subpopulations of T and B lymphocyte, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…He et al (2022) have investigated the causal effect of immune and lymphocyte cell count counts, driven by the observation that some susceptibility loci lie in genes implicated in immunological pathways or that may have immune modulatory effects. They found a statistically significant causal effect between (i) leucocyte count and MS with an IVW OR = 1.24 (95% CI: 1.07–1.43), p = .004; (ii) lymphocyte count and MS with an IVW OR = 1.17 (95% CI: 1.01–1.35), p = .03; and (iii) natural killer T (NKT) cells absolute count (AC) and MS with an IVW OR = 1.24 (95% CI: 1.06–1.45), p = .008.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al (2022) have investigated the causal effect of immune and lymphocyte cell count counts, driven by the observation that some susceptibility loci lie in genes implicated in immunological pathways or that may have immune modulatory effects. They found a statistically significant causal effect between (i) leucocyte count and MS with an IVW OR = 1.24 (95% CI: 1.07–1.43), p = .004; (ii) lymphocyte count and MS with an IVW OR = 1.17 (95% CI: 1.01–1.35), p = .03; and (iii) natural killer T (NKT) cells absolute count (AC) and MS with an IVW OR = 1.24 (95% CI: 1.06–1.45), p = .008.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, another study by Vandebergh, Becelaere, et al (2022) investigated the causal effect of IL-6 and IL-6 signalling, using both UK Biobank and CHARGE data as sources for the exposures, and showed a statistically significant causal estimate for IL-6 signalling only: OR (UK Biobank) = 1.14 (95% CI: 1.02-1.27), p = .02, and OR (CHARGE) = 1.51 (95% CI: 1.11-2.04), p = .01. He et al (2022) have investigated the causal effect of immune and lymphocyte cell count counts, driven by the observation that some susceptibility loci lie in genes implicated in immunological pathways or that may have immune modulatory effects. They found a statistically significant causal effect between (i) leucocyte count and MS with an IVW OR = 1.24 (95% CI: 1.07-1.43), p = .004; (ii) lymphocyte count and MS with an IVW OR = 1.17 (95% CI: 1.01-1.35), p = .03; and (iii) natural killer T (NKT) cells absolute count (AC) and MS with an IVW OR = 1.24 (95% CI: 1.06-1.45), p = .008.…”
Section: Circulating Interleukinsmentioning
confidence: 99%
“…All these findings suggest that peripheral immune dysregulation is a remarkable pathological marker of NDDs. With MR analysis, previous studies have also shown several blood immune cell traits are causally correlated with 4 NDDs, including AD 20, 21 , PD 21, 22, 59 , ALS 21, 23 , and MS 24, 25 . In this study, we provided new evidence that peripheral inflammatory proteins are also causally associated with NDDs, which further support the causal role of peripheral immune dysregulation in the pathogenesis of NDDs.…”
Section: Discussionmentioning
confidence: 98%
“…This finding provides further evidence for the significant involvement of peripheral immunity in the development of MS. The significance of investigating the functional roles of NKT cells in disease pathogenesis in the future is shown by the causative relationship observed between the NKT cell count and multiple sclerosis (MS) [15]. Moreover, An increased level of monocytes and T lymphocytes in the blood is linked to an increased risk of type 2 diabetes (T2D), according to studies on the role of the immune system in diabetes.…”
Section: Discussionmentioning
confidence: 99%